Statistical Analysis for Evaluating Natural Yellow Coloring Agents from Peel of Local Fruits in Malang: Mangosteen, Honey Pineapple and Red Dragon Fruits - Kurniawan, Yehezkiel Steven; Adhiwibawa, Marcelinus Alfasisurya Setya; Setiyono, Edi; Fahmi, Muhammad Riza Ghulam; Lintang, Hendrik Oktendy (Ma Chung Research Center for Photosynthetic Pigments, 2019)
In the present work, a comprehensive statistical analysis was performed to evaluate the potential application of peel of local fruits from Malang, i.e. mangosteen, honey pineapple and red dragon fruits for natural yellow coloring agents. The yellow pigments from those fruit peels were extracted through a simple maceration method using distilled water, acetone and ethanol as the solvents. The CIE color space of the extracts was measured to obtain L*, a* and b* values. The obtained data were further analyzed using Principal Component Analysis (PCA), Multivariate Analysis of Variance (MANOVA) and Duncan Test to determine the most potent natural yellow coloring agent. All the extracts were appeared as mild to strong yellow liquid except for acetone extract for the peel of red dragon fruit extracts. From the CIE color space and PCA analysis, either ethanolic or acetone extracts of mangosteen appears as a strong yellow liquid and they are statistically not different. Interestingly, the MANOVA and Duncan test results are able to distinguish that the ethanolic extract of mangosteens’ peel as the best candidate for natural yellow coloring agents because of its lowest L* and also highest b* variable values.